2020
DOI: 10.15688/ek.jvolsu.2020.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Methods for Assessing the Transition to a Green Economy

Abstract: The concept of sustainable development has become the basis for the future of humanity, and one of the tools for achieving it is green economy, which needs to be evaluated by offering certain methods of measurement. The purpose of this work is a comparative analysis of the most well-known methods for evaluating the implementation of the green economy concept at the national and regional levels, identifying their advantages and disadvantages. The analysis of foreign and domestic literature has shown that two ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Lebedeva et al compared existing GE assessment methods. The study found that current methods were mainly used to measure the "greening" of the economy [12]. To raise the efficiency of urban GE planning, researchers such as Liu have constructed a model based on an improved genetic algorithm.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Lebedeva et al compared existing GE assessment methods. The study found that current methods were mainly used to measure the "greening" of the economy [12]. To raise the efficiency of urban GE planning, researchers such as Liu have constructed a model based on an improved genetic algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…In Equation (12), j a represents the information entropy value of each indicator. n represents the sample number of each indicator.…”
Section: B Construction Of Evaluation Model For Ge Development Effici...mentioning
confidence: 99%